Chromosomal quality control in hPSCs: A practical guide to SNP array analysis with GenomeStudio - Haake, Josephine; Steenpass, Laura (Frontiers in Cell and Developmental Biology, 2025)
Human pluripotent stem cells (hPSCs) are important tools in preclinical research and disease modeling. Valid results can only be obtained using thoroughly quality-controlled hPSCs, which includes ensuring chromosomal stability. Chromosomal aberrations, which frequently arise during reprogramming, gene editing, or maintenance cultivation, can compromise the utility of these cells in research and therapeutic applications. Although traditional G-banding remains a valuable genome-wide analysis method, its limited resolution necessitates complementary approaches. SNP array analysis offers a high-resolution alternative, providing a more detailed genomic overview. We present a practical and user-friendly guide for detecting chromosomal aberrations using Illumina’s GenomeStudio, offering an easy-to-follow protocol to simplify quality control workflows for researchers with minimal bioinformatics expertise. Although SNP array analysis for hPSC quality control is not novel, this step-by-step guide highlights critical quality control metrics, thresholds, and values, streamlining the process to make it more accessible and efficient for broader adoption. In 32 hPSCs, we identified chromosomal aberrations in nine, including the frequently reported gain of 20q11.21—a common anomaly in hPSC cultures. Examples from our routine practices underscore the importance of monitoring chromosomal integrity. This guide serves as a practical resource for standardizing and enhancing quality control processes, ensuring the genomic stability of hPSCs for research and clinical applications.